1994
DOI: 10.1152/ajpcell.1994.267.3.c784
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal dissociation of ezrin during renal anoxia: role in microvillar injury

Abstract: The association/dissociation of ezrin, a microvillar membrane-cytoskeleton linker, was studied to search for the initial step leading to anoxia-induced brush-border breakdown in a rabbit proximal tubule suspension. Electron microscopy studies display time-dependent damage to the microvilli during anoxia; immunoblots demonstrate the dissociation of ezrin from the cytoskeleton, reflected by the significant decrease in Triton X-100-insoluble ezrin from control (91%) to 39% after 30 min. Simultaneously, Triton X-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 18 publications
3
52
0
1
Order By: Relevance
“…In addition, the ERM proteins are involved in membrane dynamics (11). When ezrin, radixin, and moesin were simultaneously inactivated by antisense treatment in epithelial cells, cell-cell and cell-substratum adhesion was altered (12).…”
mentioning
confidence: 99%
“…In addition, the ERM proteins are involved in membrane dynamics (11). When ezrin, radixin, and moesin were simultaneously inactivated by antisense treatment in epithelial cells, cell-cell and cell-substratum adhesion was altered (12).…”
mentioning
confidence: 99%
“…A prominent early event during renal ischemia is a distinctive pattern of proximal tubule (PT) brush border disruption consisting of clubbing, blebbing, sloughing, and internalization (3,4). This disruption has been attributed to the dissociation of the plasma membrane from the cytoskeleton within the brush border (5). Nonetheless, little is known regarding the molecular events that disrupt the association of the cell membrane with the brush border cytoskeleton.…”
mentioning
confidence: 99%
“…(iii) Ezrin has been predominantly found in F-actin-containing structures located underneath the plasma membrane in surface protrusions (12)(13)(14)(15), including the intestinal brush border (14), gastric parietal cell microvilli (16), and the renal PT brush border (5,12). (iv) During renal oxygen deprivation, there is a close temporal correlation between microvillar breakdown and the dissociation of ezrin from the microvillar cytoskeleton (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several observations suggested that ERM proteins were involved in membrane dynamics [19,20,21] . More recently, several functional analyses demonstrated that they are involved in membrane structures formation.…”
Section: Erm: Functional Insight: 81 Formation Of Cell Surfacementioning
confidence: 99%